The Relationship between the Character of the Mother in Labor and the Retention of the Placenta at the Afisya Clinic, Hamlet III, Melur, Sambirejo East village, Percut Sei Tuan District Deli Serdang Regency 2017 - 2021 - Sri Rezeki; Erin Padilla Siregar (Science Midwifery, 2022)
Retention of the placenta is a delay in the delivery of the placenta for thirty minutes after the birth of the baby. In some cases, recurrent placental retention (habitual retention of the placenta) may occur. The placenta must be delivered immediately because it can cause complications such as bleeding, infection as a result of inanimate objects, placental incarceration can occur, can cause placental polyps, and malignant degeneration of choriocarcinoma. Afisya Clinic, Hamlet III Melur, East Sambirejo Village, Percut Sei Tuan District, Deli Serdang Regency, 2017-2021. The study was conducted at the Afisya clinic from January to June 2022. The type of research was descriptive analytical with case control. The population and sample were 92 with nonprobability sampling technique or saturated sample, the research instrument was clinical records or medical records. Data processing by editing, coding, tabulating, and data entry. The results of the univariate analysis showed that of the 92 mothers who experienced retained placenta, the majority of mothers with Retention Placenta were at mild risk as many as 83 respondents (90.2%). The majority of the age at risk were 50 respondents (54.3%). (54.3%) The majority of risky delivery distances were 48 respondents (52.2%). From the results of the statistical test, the Odds Ratio (OR) = 0.128. 95% CI = 0.015-1.070 and P value 0.036 <0.05, which means that there is a significant relationship between maternal age characteristics and the incidence of retained placenta. From the results of the statistical test, the value of Odds ratio (OR) = 0.128. 95% CI = 0.015-1.070 and P value 0.036 <0.05, which means that there is a significant relationship between maternal parity characteristics and the incidence of retained placenta. From the results of the statistical test, the value of Odds ratio (OR) = 0.116. 95% CI = 0.014-0.972 and P value 0.032 <0.05, which means that there is a significant relationship between the characteristics of the distance between the mother and the incidence of retained placenta. It can be used for clinicians as knowledge, and more often provides counseling during pregnancy in an effort to detect early and can prevent complications during childbirth.